Let's analyze Oliver's work step by step.
The original quadratic equation is:
\[ (x + 3)(x + 4) = 0 \]
To solve for \(x\), we set each factor equal to zero:
- \(x + 3 = 0\) → \(x = -3\)
- \(x + 4 = 0\) → \(x = -4\)
Now, let's check Oliver's work. Here is the breakdown of what he wrote:
- He wrote:
\(x - 3 = 0\) (This is incorrect since the factor should be \(x + 3 = 0\)) \(x + 4 = 0\) (This is correct) - He found:
\(x = 3\) (This is incorrect since it should be \(x = -3\))
\(x = 4\) (This is correct but corresponds to the wrong factor)
From his work, we can identify the following issues:
- He incorrectly set \(x - 3 = 0\) instead of \(x + 3 = 0\).
- The values he found, \(x = 3\) and \(x = 4\), do not match the correct solutions, which are \(x = -3\) and \(x = -4\).
Thus, the correct option among those provided would be:
3. No, x - 3 = 0 in the second row should be x + 3 = 0.